Formulation of Food Bar Based on Tilapia (Oreochromis niloticus) and Seaweed (Eucheuma cottoni) Flours as Nutritional Food - Rahmi Rahmi; Ikhsanul Khairi; Sri Ayu Insani; Nabila Ukhty; Uswatun Hasanah; Syarifah Zuraidah; Benny Manullang; Anhar Rozi; Akbardiansyah Akbardiansyah (Jurnal Ilmiah Samudra Akuatika, 2025)
Food bars are compact, bar-shaped food products with high nutritional value and potential to meet human nutritional needs. The development of food bars represents an effort to create functional food products that contribute to human health. This study aimed to determine the optimal food bar formulation based on hedonic evaluation and to investigate the sensory, physical, and chemical characteristics of the resulting products. Three formulations were prepared: F1 (15 g tilapia fish flour and 10 g seaweed flour), F2 (12.5 g tilapia fish flour and 12.5 g seaweed flour), and F3 (10 g tilapia fish flour and 15 g seaweed flour). The quality evaluation of the food bars included hedonic testing, bulk density analysis, and proximate analysis. The hedonic test results indicated that formulation F1 obtained scores of 3 for texture, 3 for color, 2 for taste, and 3 for aroma; formulation F2 obtained scores of 3 for texture, 3 for color, 2 for taste, and 3 for aroma; whereas formulation F3 obtained scores of 3 for texture, 4 for color, 3 for taste, and 3 for aroma. The bulk density values were 0.54 g/mL for F1, 0.54 g/mL for F2, and 0.53 g/mL for F3. Proximate analysis showed that formulation F1 contained 33.67% moisture, 54.67% ash, 29.67% protein, 32.00% fat, and 22.67% carbohydrates. Formulation F2 contained 41.67% moisture, 54.67% ash, 29.33% protein, 34.33% fat, and 37.00% carbohydrates, while formulation F3 contained 37.67% moisture, 53.67% ash, 29.33% protein, 34.00% fat, and 44.00% carbohydrates. Based on the hedonic evaluation, formulation F3 (10 g tilapia fish flour and 15 g seaweed flour) was identified as the best formulation. Panelists’ acceptance of texture, taste, and aroma was categorized as slightly disliked, while color was categorized as liked.